Case study: Carrapateena caveback propagation and recovery - Poulter, M.; Ormerod, T.; Balog, G.; Cox, D. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The Carrapateena sublevel cave (SLC) experienced a significant challenge between late 2020 and 2022 when cave propagation stalled within the Woomera Shale. In November 2020, following ten months of steady growth, the caveback rapidly grew without incident through the competent Upper Whyalla Sandstone into the overlying shale, growing 152 m vertically within 24 hours. However, from December 2020, vertical growth ceased despite ongoing draw, resulting in a steadily increasing airgap above the muckpile. By mid-2021, the airgap height exceeded 110 m, necessitating intervention to prevent further escalation, and to preserve safety and mine production. The cave stall was attributed to multiple factors including uneven height of draw creating a buttressed ‘verandah’, stress redistribution limiting failure in the shale and the nature of the shale, which was a weak, highly laminated rock mass. A multifaceted recovery strategy was implemented. Production was reprioritised to target draw beneath the underbroken verandah. Ring extensions were targeted to increase the undercut hydraulic radius. Extensive conditioning of the ground from surface was conducted and drilling commenced for mass blasting. These actions successfully induced caving activity and resulted in further cave growth over the next two years. Breakthrough to surface occurred in December 2022 with a minor seismic response, no observed airblast and minimal impact to mine production, marking a major milestone for Carrapateena. The successful recovery was enabled by an extensive cave monitoring system array, allowing responses to cave engineering to be analysed quickly, and then used to inform plans and risk level sensitivities. Lessons learned in managing a cave stall include the critical role of understanding the rock mass in a cave column, the importance of real-time monitoring and employing adaptive draw strategies. This case study provides valuable insights for cave operations encountering propagation issues in highly laminated sedimentary rock masses specifically.